Expanding the debate about content moderation: Scholarly research agendas for the coming policy debates - Tarleton Gillespie; Patricia Aufderheide; Elinor Carmi; Ysabel Gerrard; Robert Gorwa; Ariadna Matamoros-Fernández; Sarah T. Roberts; Aram Sinnreich; Sarah Myers West (Internet Policy Review, 2020)
Content moderation has exploded as a policy, advocacy, and public concern. But these debates still tend to be driven by high-profile incidents and to focus on the largest, US based platforms. In order to contribute to informed policymaking, scholarship in this area needs to recognise that moderation is an expansive socio-technical phenomenon, which functions in many contexts and takes many forms. Expanding the discussion also changes how we assess the array of proposed policy solutions meant to improve content moderation. Here, nine content moderation scholars working in critical internet studies propose how to expand research on content moderation, with implications for policy.
Keywords: 300; Content moderation; Platforms; Internet policy; Social media; Regulation